Two Cases of Lower Body Contouring with a Spiral and Vertical Medial Thigh Lift - Sang Wha Kim; Hyun Ho Han; Je Won Seo; Jung Ho Lee; Deuk Young Oh; Sang Tae Ahn; Jong Won Rhie (Archives of Plastic Surgery, 2012)
Massive weight loss results in skin excess, leading to an unsatisfying body contour. Various thigh lift procedures can correct flabby skin in the lower leg. We present a lower body contouring technique with a report on two patients. The procedure is determined by the body contour of the patient. As the skin excess in the thigh area tended to appear mostly on the medial side, a vertical medial thigh lift was considered. Moreover, for patients with a pear/guitar-shaped body contour, we added the spiral thigh lift for skin excess in the buttocks and the lateral thigh area. The extent of tissue to excise was determined by pinching the patient in a standing position. The inferior skin flap was fixed to non-movable tissue, which was helpful for lifting the tissue and preventing the widening of the scar. After the operation, a drain was kept for 3 to 4 days. A compressive garment was used after removing the drain. There were no complications. The patients were discharged 6 to 8 days after the operation. In conclusion, skin excess, especially in the lower body, can be corrected by a thigh lift combining several procedures, varying from person to person.